Sustainable & responsible investing 360° lessons learned from world class investors - Arnell, R. Scott, 1957- (Rowman & Littlefield, 2022)
"A must-read for anyone struggling to understand Impact Investing, ESG, SRI, and the myriad terms used to describe investing for positive impact. Hear from 27 experts managing trillions in funds about why sustainable and responsible investing matters, how they perform, and what the future of this investment strategy is"--